Formation of Water Resources Market: Conditions and Prerequisites; SGEM. 2nd International Multidisciplinary Scientific Conference on Social Sciences and Arts; Bk. 2, Vol. 3 - Kozlova N. V. Nataliya Vladislavovna (Economics and Tourism, 2015)
Title screen